Comparison of altruistic, egoistic, and scientific appeals in the recruitment of politicians to a survey panel - Lauri Rapeli; Kim Backström (PLoS ONE, 2026)
Low survey participation is a persistent problem for all survey researchers. Unlike citizens, politicians are seldom targeted for surveys. Politicians often are not prepared to participate, which leads to a lack of understanding regarding their willingness to collaborate in surveys. This study presents a rare survey recruitment experiment where 7,397 local-level politicians from Finland were randomly assigned to groups that received by e-mail 1) an altruistic or 2) an egoistic appeal or 3) an appeal referring to benefits for science when they were invited to participate in the Finnish Politician Panel. Overall, we find no differences in collaboration rates, suggesting that in politician samples the altruism-egoism framework is largely irrelevant and that for maximizing participation rates among politicians, survey researchers should look into alternative methods. However, politicians who are older, live in urban municipalities and represent the political left are more likely than their counterparts to volunteer as panel participants.